2023
DOI: 10.3390/healthcare11212830
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shock Wave Therapy for the Treatment of Musculoskeletal Pain: A Narrative Review

Hortensia De la Corte-Rodríguez,
Juan M. Román-Belmonte,
Beatriz A. Rodríguez-Damiani
et al.

Abstract: Extracorporeal shock waves are high-intensity mechanical waves (500–1000 bar) of a microsecond duration with a morphology characterized by a rapid positive phase followed by a negative phase. Background: Extracorporeal shock waves have been used for pain treatment for various sub-acute and chronic musculoskeletal (MSK) problems since 2000. The aim of this article is to update information on the role of extracorporeal shock wave therapy (ESWT) in the treatment of various pathologies that cause MSK pain. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 94 publications
1
2
0
Order By: Relevance
“…The ANN model was useful for guiding authors in recommending ESWT, with high predictive ability and an anticipation of the outcome based on patients’ characteristics [ 22 ]. The results revealed that age before ESWT was the most influential factor in deciding the probability of success of MCST; this finding agrees with another paper, cited in a recent review [ 47 ], where it was noted that the greater probability of success had been achieved by the youngest participant [ 48 ]. However, the CMS score, VAS, and RM at the time of the ESWT were also very influential factors in deciding the probability of success of the minimum clinically successful therapy (MCST), that is, a reduction in VAS of 40% from the baseline.…”
Section: Discussionsupporting
confidence: 90%
“…The ANN model was useful for guiding authors in recommending ESWT, with high predictive ability and an anticipation of the outcome based on patients’ characteristics [ 22 ]. The results revealed that age before ESWT was the most influential factor in deciding the probability of success of MCST; this finding agrees with another paper, cited in a recent review [ 47 ], where it was noted that the greater probability of success had been achieved by the youngest participant [ 48 ]. However, the CMS score, VAS, and RM at the time of the ESWT were also very influential factors in deciding the probability of success of the minimum clinically successful therapy (MCST), that is, a reduction in VAS of 40% from the baseline.…”
Section: Discussionsupporting
confidence: 90%
“…Following exercise, increased (in relation to baseline) experience of activeness and sinewiness was felt in the torso area, whereas experience of relaxation was increased in the head area. Sensations of pain and discomfort decreased in shoulder and back area, supporting the role of exercise in pain management [45]. Interestingly, experience of exhaustion increased in the lower limbs but decreased in the head area, likely reflecting the mental component of the exertion.…”
Section: Bodily Sensations and Physical Exercisementioning
confidence: 65%
“…Several studies have demonstrated the safety and effectiveness of ESWT in pain relief, clinical improvements and calcification resorption in patients with RCCT (Auersperg & Trieb, 2020;De la Corte-Rodríguez et al, 2023;Ioppolo et al, 2014). The mechanism of action and effects of F-and R-SWT may differ because the bioeffects are related to the pressure waveform (Moya et al, 2018;d'Agostino et al, 2015).…”
Section: Introductionmentioning
confidence: 99%